KEDUDUKAN HUKUM KOMISARIS BERDASARKAN UNDANG-UNDANG NOMOR 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS - Annora Arsan; Hasniati Fahmi (VERITAS, 2021)
Pursuant to Article 1 number 6 of Law Number 40 of 2007 concerning Limited Liability Companies, a Commissioner is an organ of the Company whose task is to carry out general and / or special supervision in accordance with the articles of association and provide advice to the Board of Directors. In principle, the role of the Commissioners is actually to supervise and provide advice to the Directors. However, individual commissioners do not have significant power in supervising directors. From the research results, it can be concluded that the Legal Position of Commissioners based on Law Number 40 of 2007 concerning Limited Liability Companies is that the Commissioners must be able to wisely manage various conflicts as a result of differences in the interests of shareholders. However, in practice, the responsibility of the Commissioner to manage these differences of interest can take various forms, for example making various agreements that benefit the company, not hiding information for personal gain, not abusing trust and not engaging in unfair competition. Commissioners are fully responsible for the management and operation of the company for the interests and goals of the company. In carrying out these duties, Commissioners are given full rights and powers, with the consequence that every action and action taken by the directors will be considered and treated as the company's actions and actions, as long as they act in accordance with what is stipulated in the company's articles of association. Abstrak Berdasarkan Pasal 1 angka 6 Undang-Undang Nomor 40 Tahun 2007 tentang Pereroan Terbatas, Komisaris adalah Organ Perseroan yang bertugas melakukan pengawasan secara umum dan/atau khusus sesuai dengan anggaran dasar serta memberi nasihat kepada Direksi. Secara prinsip, peran Komisaris sebenarnya adalah melakukan pengawasan dan memberi nasihat kepada Direksi. Namun, komisaris secara individu tidak punya kekuatan yang berarti dalam mengawasi direksi. Dari hasil penelitian dapat disimpulkan Kedudukan Hukum Komisaris Berdasarkan Undang-Undang Nomor 40 Tahun 2007 Tentang Perseroan Terbatas adalah Komisaris harus mampu mengelola secara bijak berbagai pertentangan sebagai akibat adanya perbedaan kepentingan para pemegang saham. Namun, dalam pelaksanaannya, tanggung jawab Komisaris pengelolaan perbedaan kepentingan ini dapat muncul dalam berbagai bentuk, misalnya membuat berbagai perjanjian yang menguntungkan perseroan, tidak menyembunyikan suatu informasi untuk kepentingan pribadi, tidak menyalahgunakan kepercayaan dan tidak melakukan kompetisi yang tidak sehat. Komisaris bertanggung jawab penuh atas pengurusan dan jalannya perseroan untuk kepentingan dan tujuan perseroan. Di dalam menjalankan tugasnya tersebut, Komisaris diberikan hak dan kekuasaan penuh, dengan konsekwensi bahwa setiap tindakan dan perbuatan yang dilakukan oleh direksi akan dianggap dan diperlakukan sebagai tindakan dan perbuatan perseroan, sepanjang mereka bertindak sesuai dengan apa yang ditentukan dalam anggaran dasar perseroan.